Student Needs, Employment Realities, and PhD Program Design in Canada: The Case of Planning PhD Programs - Ross, Timothy; Mah, Julie; Biggar, Jeff; Zwick, Austin; Modlinska, Ewa (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2018)
PhD graduates in Canada routinely find themselves considering employment outside academia. This paper explores PhD program design in relation to PhD students’ employment realities through a case study of Canadian planning PhD programs. Two questions guided the study: (1) How could planning PhD programs be redesigned to prepare students for a wider variety of career options post-graduation? And (2) What are some of the institutional challenges hindering PhD program reform? To engage these questions, we surveyed planning PhD students and program directors, gathered email input from planning practitioners, and held a workshop and roundtable at two different academic conferences. Findings suggest that program reforms, such as offering more external research partnership opportunities to PhD students, could help to better support multiple career pathways for PhD students. Our findings also suggest that planning scholars and practitioners need to question their views of the academia–practice relationship and PhD students’ roles and aims.